2018
DOI: 10.1016/j.apergo.2017.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms associated with reading from a smartphone in conditions of light and dark

Abstract: Asthenopia symptoms were investigated in visually-normal subjects without computer-related vision symptoms after prolonged reading from: smartphone versus hardcopy under photopic conditions, and smartphone in conditions of ambient versus dark room illumination. After reading from the smartphone, total symptom scores and nine out of ten questionnaire symptoms were significantly worse than for the hardcopy ("blurred vision while viewing the text, "blurred distance vision after the task", "difficulty in refocusin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(55 citation statements)
references
References 32 publications
4
48
0
3
Order By: Relevance
“…Examples of non-optimal conditions which could be experienced by mobile workers include working near windows or luminaires which are significantly brighter than the digital display, or the reverse: using a digital display in low light conditions where the display is significantly brighter than the surroundings. In a study comparing smartphone use in dark versus lit conditions, visual symptoms and eye discomfort was greater when reading from a smartphone in the dark [30]. Antona and coauthors comment that although smartphone devices may have an auto-brightness function which automatically adjusts the screen luminance to match the ambient lighting conditions, they have observed that the screen luminance is too great when using the smartphone in the dark [30].…”
Section: Lightingmentioning
confidence: 99%
See 1 more Smart Citation
“…Examples of non-optimal conditions which could be experienced by mobile workers include working near windows or luminaires which are significantly brighter than the digital display, or the reverse: using a digital display in low light conditions where the display is significantly brighter than the surroundings. In a study comparing smartphone use in dark versus lit conditions, visual symptoms and eye discomfort was greater when reading from a smartphone in the dark [30]. Antona and coauthors comment that although smartphone devices may have an auto-brightness function which automatically adjusts the screen luminance to match the ambient lighting conditions, they have observed that the screen luminance is too great when using the smartphone in the dark [30].…”
Section: Lightingmentioning
confidence: 99%
“…In a study comparing smartphone use in dark versus lit conditions, visual symptoms and eye discomfort was greater when reading from a smartphone in the dark [30]. Antona and coauthors comment that although smartphone devices may have an auto-brightness function which automatically adjusts the screen luminance to match the ambient lighting conditions, they have observed that the screen luminance is too great when using the smartphone in the dark [30].…”
Section: Lightingmentioning
confidence: 99%
“…These symptoms are related to screen size, small writing, the use of smartphones in dark places, and the tendency to focus when looking at the smartphone screen, which affects the visual organ's workload. 13 Eye fatigue symptoms are closely related to the blue light emitted by the light-emitting diode (LED) ORIGINAL RESEARCH ARTICLE (LED) on the smartphone screen. Even though it looks like white light, the light emitted by a lightemitting diode (LED) has a 400 -490 nm wavelength, which falls into the blue light category.…”
Section: Introductionmentioning
confidence: 99%
“…In previous research, eye fatigue was measured through a questionnaire [ 3 , 4 , 5 ]. However, since this questionnaire is based on the subjective thinking of the user, it is difficult to guarantee its reliability.…”
Section: Introductionmentioning
confidence: 99%